AI AGENTS IN SALES FUNNEL OPTIMIZATION - Литвинчук, Ольга (SWorldJournal, 2025)
The article analyzes the implementation of multitasking artificial intelligence agents in the sales funnel – from automating the lead nurturing process to detecting hidden patterns in both small and large datasets. The scientific novelty lies in the first